Multidimensional redox potential/pKacoupling in multicopper oxidases from molecular dynamics: implications for the proton transfer mechanism - Santo, Anderson A. E. [UNESP]; Lazaroti, Vitor Hugo R. [UNESP]; Feliciano, Gustavo T. [UNESP] (Royal Society of Chemistry (RSC), 2021)
Bilirubin oxidases (BOD) are metalloenzymes that catalyze the conversion of O2and bilirubin to biliverdin and water in the metabolism of chlorophyll and porphyrin. In this work we have used the CpHMD method to analyze the effects of the different oxidation states on the BOD trinuclear cluster (TNC). Our results demonstrate that there is a link between the different oxidation states of copper ions and the protonation capacity of nearby titratable residues. Each configuration affects pKadifferently, creating proton gradients within the enzyme that act in an extremely orderly manner. This order is closely linked to the catalytic mechanism and leads us to the conclusion of the entry of the O2molecule and its reduction in water molecules is associated with the probability of the release of protons from nearby acid groups. With this information, we deduce that under the initial reaction conditions the acidic side chains of nearby residues can be protonated; this allows the enzyme to reduce the activation energy of the reaction by coupling the proton transfer to oxidation state changes in the metallic center.